Can ductus arteriosus morphology influence technique/outcome of stent treatment?. Issue 6 (17th January 2020) - Roggen, Mieke; Cools, Bjorn; Brown, Stephen; Boshoff, Derize; Heying, Ruth; Eyskens, Benedicte; Gewillig, Marc
Abstract: Introduction: Results and outcomes of ductus arteriosus stenting vary widely. The aim of this study was to determine whether ductus morphology is associated with different procedural outcome. Methods: Over an 18‐year period, 123 patients presented with ductal dependent pulmonary blood flow. Results were retrospectively assessed based on radiographic anatomic features of the ductus arteriosus: Group 1: "straight" ductus arteriosus, typically seen in patients with Pulmonary atresia with intact septum (PA‐IVS), Group 2: "intermediate" ductus arteriosus as seen in severe pulmonary stenosis (PS)‐single ventricle, Group 3: "vertical" ductus arteriosus typically seen in patients with pulmonary atresia‐ventricular septal defect, Group 4: ductus arteriosus arising from the aorta to a single lung, Group 5: ductus arteriosus arising from the innominate/subclavian artery to a single lung, Group 6: ductus arteriosus from innominate/subclavian artery to both lungs. Results: Ductal stenting (DS) was attempted in 98 patients with 99 ducts. Successful stenting was possible in 83 patients. Success of DS was significantly different among the groups ( p = .04, F = 5.41). Groups 1, 4, and 5 were "easy" with good success while Groups 2, 3, and 6 were complex and demanding. There were two deaths (after 5 and 7 days, respectively) that could be ascribed to DS. Elective re‐interventions were performed in 34 ductuses (40%). Fifty three percent ( n = 44/83) of successful ductus stents proceeded to further surgery and 20 ducts closed spontaneously in asymptomatic patients over time. Conclusions: Ductus arteriosus morphology influences technique and determines complexity, safety, and final outcome of ductus arteriosus stenting.